1-2-3! Catch-Up for HPV: A Theoretically Informed Pilot Intervention to Increase HPV Vaccine Uptake among Young Adults. Issue 2 (4th March 2023) - Harper, Kristina; Short, Mary B.; Bistricky, Steven; Kusters, Isabelle S.
ABSTRACT: Background: Human Papillomavirus (HPV) is the most common sexually transmitted infection. Current guidelines recommend HPV vaccination during adolescence, but vaccination rates remain suboptimal. Efforts are needed to increase vaccination among the catch-up group (individuals aged 18–26 years). Interventions have primarily focused on education, with minimal success. Purpose: This study enhanced an education-based intervention to directly target Theory of Planned Behavior (TPB) variables and increase catch-up group HPV vaccination. Methods: Using a randomized control design, a TPB-informed psychosocial intervention (n = 41) was compared to education-only (n = 35) and no-intervention control groups (n = 35). Results: HPV knowledge, HPV Vaccine knowledge, attitudes, subjective norms, vaccination intention, and vaccination uptake were all more profoundly improved in the TPB-informed intervention. Further, regression models including knowledge and TPB variables predicted intention 1 week later ( F (6, 110) = 17.13, p < .001) and uptake 6 months later (χ 2 = (7, N = 46) = 25.12, p = .001), accounting for 42–67% of the variance. Discussion: These outcomes provide support for disseminating TPB-informed interventions to the catch-up group on college campuses. Translation to Health Education Practice : Interventions for HPV vaccination uptake should include both education and TPB factors to address barriers. A AJHE Self-Study quiz is online for this article via the SHAPE America Online Institute (SAOI) http://portal.shapeamerica.org/trn-Webinars